A Chronotopic Study of Ephemerality in Virginia Woolf’s To the Lighthouse - FERCHANE, Rofeida; SELT ,Afaf Djihad (Faculty of Letters and Foreign Languages Department of English, 2017)
The interplay of “Time and space” is thought to be one of the significant aspects in the analysis of modernist literary works. The Russian theorist Mikhail Bakhtin postulates that these two components have got equal prominence and he has accordingly coined the term “chronotope” which includes the combination of time and space along with their crucial role in apprehending time‟s ephemerality. The act of reading and understanding a narrative is possible because of the recognition of the fact that any literary work‟s plotline has duration in „real life‟ and ascribes a sort of temporality to the narrative as a whole. This reading experience is made intricate in To the Lighthouse (1927), which concerns itself mostly with the thoughts and associations of the characters. In this research, the idea of an instinctive understanding of time is developed further in combination with the stream of consciousness that describes the flow of thoughts inside the mind of the characters. On this basis, the present dissertation examines the expansions and contractions of the narrated time in the novel and how they serve to illustrate the subjective human experience of time passing. Added to that, it investigates this visualisation of the narrative structure and the way it is aided by the central constitutive metaphors, relying on Bakhtin‟s chronotope that is illustrated in the novel. Finally, this dissertation extends to extract these indicators from Virginia Woolf‟s novel and analyzes them according to the literary technique of stream of consciousness.